Patuh dan Acuh Tak Acuh: Respons Masyarakat terhadap Komunikasi Kebijakan Penanganan Covid-19 Pemerintah Provinsi Bali - Gede Suardana; Ni Wayan Widhiasthini (Jurnal Kajian Bali (Journal of Bali Studies), 2022)
Effective communication strategies are needed in handling Covid-19. The Bali Provincial Government uses a ritual-based communication strategy in its Covid-19 handling policies. This study aims to examine the effectiveness of the communication strategy on the level of community compliance. The conducted qualitative research was from April 2020 to August 2021. In-depth interviews with council of the Parisada Hindu Dharma Indonesia (PHDI) Bali, Traditional Village Assembly (MDA) Bali, and the community. Observation of public response and study of mass media and social media literature. The data were analyzed using a critical approach to cultural studies emphasizing ritual-based communication strategies and community responses. The results showed a change in the community's comeback from a high level of compliance to indifference. This article offers a message that the priest must convey ritual-based communication as a referent of power, not otherwise taken over by structural strength so that the community still obeys the directive.